Class, identity, integration, and the two-tiered peace process - Holland, Curtis C. (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2023)
This article critically examines the extent to which increases in socio-economic equality between Protestants and Catholics over the post-Agreement period has corresponded to a gradual de-centering of ethnopolitical identity in social relations and political processes. I argue that, while there has been an increase in social integration and moderate growth in the political middle ground, such trends are not experienced equally across class contexts. On an everyday basis, ethnopolitical identity is most strongly felt in relatively deprived and religiously segregated communities who have experiencing very little by the way of peace dividends and suffering disproportionately and intergenerationally from conflictrelated trauma and an ongoing sense of sectarian threat.
Keywords: družbeni razredi; identiteta; integracija; neenakost; revščina; Severna Irska; Velikonočni sporazum